(untitled) (Baghdad Science Journal, 2020)
Titanium dioxide nanotubes were synthesized by anodizing Ti sheets in the ethylene glycol solution and were covered in Pt nanoparticles onto the surface of TiO2NTs using electrodeposition method from using five derivatives of Mannich base Pt complexes which have been used as precursor of platinum. The mean size, shape, elemental composition of the titanium dioxide nanotubes and platinum deposited on the template were evaluated by different techniques such as field emission scanning electron microscope (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction pattern (XRD), and energy dispersive X-ray (EDX) technique. From all these analyses, the TiO2NTs prepared and Ptnanoparticles deposited on it were identified. The diagnoses proved that all the Pt nanoparticles have a size less than 50 nm. The MCF-7 cancer cell lines and WRL68 normal cell lines were treated with concentration 800, 400,200,100, 50, 25, 12.5µgof TiO2NTs and Pt2NTs(1) and (2) for 48hours using MTT assay.IC50 and inhibition rate were calculated. The result shows that the Pt2NTs have more inhibition effect on cancer cell lines than TiO2NTs array.